2017
DOI: 10.1165/rcmb.2014-0482oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prenatal versus Postnatal Vitamin D Deficiency on Pulmonary Structure and Function in Mice

Abstract: Epidemiologic studies have linked gestational vitamin D deficiency to respiratory diseases, although mechanisms have not been defined. We hypothesized that antenatal vitamin D deficiency would impair airway development and alveolarization in a mouse model. We studied the effect of antenatal vitamin D deficiency by inducing it in pregnant mice and then compared lung development and function in their offspring to littermate controls. Postnatal vitamin D deficiency and sufficiency models from each group were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Genomic studies showed that 1,25‐dihydroxyvitamin D, the biologically active form, already in these stages of lung development influences the expression of genes, which have previously been associated with lung development and asthma pathogenesis . Furthermore, in vivo mice studies reported that in utero 25‐hydroxyvitamin D deficiency can result in a reduced lung volume, a diminished tracheal diameter and alveolar simplification, as well an altered lung function with increased airway resistance and decreased pulmonary compliance . Our observations that higher 25‐hydroxyvitamin D concentrations are associated with a higher FVC are in line with these studies.…”
Section: Discussionsupporting
confidence: 89%
“…Genomic studies showed that 1,25‐dihydroxyvitamin D, the biologically active form, already in these stages of lung development influences the expression of genes, which have previously been associated with lung development and asthma pathogenesis . Furthermore, in vivo mice studies reported that in utero 25‐hydroxyvitamin D deficiency can result in a reduced lung volume, a diminished tracheal diameter and alveolar simplification, as well an altered lung function with increased airway resistance and decreased pulmonary compliance . Our observations that higher 25‐hydroxyvitamin D concentrations are associated with a higher FVC are in line with these studies.…”
Section: Discussionsupporting
confidence: 89%
“…Experimental and human studies have revealed vitamin D to play a key role in lung maturation by modulating type II alveolar cell differentiation and by stimulating surfactant synthesis and release . Antenatal vitamin D deficiency impairs airway and alveolar development and limits lung function in mice . Moreover, vitamin D deficiency may provoke proliferation and hypertrophy of smooth muscle, contributing to airway remodeling and increased airway smooth muscle mass …”
Section: Possible Explanations Of Findingsmentioning
confidence: 99%
“…[62][63][64][65] Antenatal vitamin D deficiency impairs airway and alveolar development and limits lung function in mice. 9 Moreover, vitamin D deficiency may provoke proliferation and hypertrophy of smooth muscle, contributing to airway remodeling and increased airway smooth muscle mass. 66 Thus, an adequate prenatal vitamin D status could turn into beneficial effects on lung function and reduction in lung reactivity to diverse environmental triggers.…”
Section: P Oss Ib Le E Xpl Anati On S Of Finding Smentioning
confidence: 99%
“…First, VDRs are present in immune cells and the airways [86]. Second, vitamin D plays multiple effects on foetal maturation and the developing immune system [87,88]. Third, polymorphisms in VDR and metabolism genes are associated with childhood asthma susceptibility [89,90].…”
Section: Prenatal Vitamin D Status and Asthma Riskmentioning
confidence: 99%